Influence of phosphorous on nucleation and growth of grains during solidification in a NiCrFe alloy. Issue 1 (January 2019) - Lian, Xintong; Sun, Wenru; Chang, Litao; Liu, Fang; Xin, Xin
Abstract: The influence of phosphorus on the solidification of a NiCrFe model alloy has been investigated through a series of analytical techniques. It was found that increasing phosphorous additions greatly influenced the as-cast microstructure, changing from equiaxed grains to columnar grains in the center of ingots. It is indicated that the increase of phosphorous reduced the nucleation of grains and promoted dendrite growth during solidification. Furthermore, the addition of phosphorus in alloys also caused the segregation and phase transformation at grain boundaries and in interdendritic regions. The mechanism by which phosphorus influence the solidification of alloys was discussed based on experimental results as well.